Development and validation of a multi-angle light scattering method for fast engine soot mass and size measurements. Issue 9 (1st September 2020) - Kheirkhah, Pooyan; Baldelli, Alberto; Kirchen, Patrick; Rogak, Steven
Abstract: A Fast Exhaust Nephelometer (FEN) is developed for light scattering measurement of particles produced by unsteady combustion processes, such as in diesel engines. The FEN simultaneously measures the light scattering intensity at three angles to infer the mass concentration ( C m ), the geometric mass mean mobility diameter ( d m, g ), and the geometric standard deviation ( σ m, g ) of polydisperse soot. A kernel is used to determine C m, d m, g, and σ m, g based on lookup tables generated with the Rayleigh-Debye-Gans light scattering model for fractal aggregates (RDGFA); the model incorporates the variation of the primary particle size ( d p ) with aggregate size ( d a ), and nine parameters related to the soot properties, and one to the FEN optics. These parameters are determined a priori from literature and Transmission Electron Microscopy (TEM). The inverted C m and d m, g are within ±10% of the gravimetric mass concentration and SMPS mobility diameter. This, however, largely depends on the choice of the parameters used to generate the lookup tables. A parametric study shows the inferred mass is most sensitive to uncertainties in the soot refractive index, the primary particle size, and the fractal pre-factor k f . Considering the wide range of soot refractive indices in the literature and the sensitivity of the morphological parameters to the processing of soot images, the uncertainty in mass concentration would be over 40%. Because of this, a novel approach of relating the size of primary particles to the size of aggregates is incorporated for the first time in the light scattering model, and reduces the uncertainty to ±25–30%. Copyright © 2020 American Association for Aerosol Research